2023
DOI: 10.1002/jad.12146
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sexual orientation identity development in plurisexual versus monosexual latinx sexual minority youth

Abstract: Introduction: Plurisexual individuals represent 50% of sexual minority adolescent communities. However, most studies of sexual minority adolescents analyze this population as a homogeneous group rather than attending to plausible differences between plurisexual and monosexual sexual minority youth. This study examined whether plurisexual Latinx youth differed from monosexual youth on three facets of sexual orientation identity (SOI) development (exploration, resolution, and affirmation). Further, we examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Similar to the general social support, on days when SMY received more supportive messages about their sexual identity (i.e., LGBTQ-specific identity affirmation), they also experienced more positive affect and less negative affect. Our results build upon past cross-sectional research that has revealed associations between LGBTQ-identity specific affirmation and reduced depression and greater self-esteem (Busby et al, 2020; Hainsworth et al, 2023). These findings also provide evidence for sexual minority resilience theories (Kwon, 2013; Meyer, 2015; Perrin et al, 2020), such that feeling positively about one’s marginalized identity may portend beneficial mental health outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to the general social support, on days when SMY received more supportive messages about their sexual identity (i.e., LGBTQ-specific identity affirmation), they also experienced more positive affect and less negative affect. Our results build upon past cross-sectional research that has revealed associations between LGBTQ-identity specific affirmation and reduced depression and greater self-esteem (Busby et al, 2020; Hainsworth et al, 2023). These findings also provide evidence for sexual minority resilience theories (Kwon, 2013; Meyer, 2015; Perrin et al, 2020), such that feeling positively about one’s marginalized identity may portend beneficial mental health outcomes.…”
Section: Discussionsupporting
confidence: 83%